PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PKN DI KELAS IV SD NEGERI 2 LAMCOT - Lia Azkiya; Mislinawati; Nurmasyitah (STKIP Subang, 2026)
This classroom action research is motivated by the low Civics learning outcomes of fourth-grade students at SD Negeri 2 Lamcot due to monotonous, teacher-centered methods, which resulted in an initial classical mastery of only 23.8%. This study aims to improve student activities and learning outcomes on the subject of Pancasila as the state foundation by implementing the Problem-Based Learning (PBL) model across two cycles. The research subjects consisted of 24 students, with data gathered through observation sheets and cognitive tests. The primary focus of the results demonstrates a significant performance increase in each cycle. The teacher's instructional score improved from 2.8 (good) to 3.7 (excellent). Concurrently, student active engagement escalated from 43.18% (fair) to 83.82% (excellent). Accumulatively, the students' post-test average score rose sharply from 62.97 with 58.33% classical mastery in cycle I to 89.17 with 91.67% classical mastery by the end of cycle II. In conclusion, the strategic implementation of the PBL model empirically and effectively enhances student learning activities and cognitive achievements in a sustainable manner